A Systematic Study of Fluorescence‐Based Detection of Nitroexplosives and Other Aromatics in the Vapor Phase by Microporous Metal–Organic Frameworks. Issue 47 (10th October 2013) - Pramanik, Sanhita; Hu, Zhichao; Zhang, Xiao; Zheng, Chong; Kelly, Sean; Li, Jing
Abstract A systematic study is conducted on four microporous metal–organic framework compounds built on similar ligands but different structures, namely [Zn3(bpdc)3(bpy)]⋅4 DMF⋅H2O (1), [Zn3(bpdc)3(2, 2′dmbpy)]⋅4 DMF⋅ H2O (2), [Zn2(bpdc)2(bpe)]⋅2 DMF (3), and [Zn(bpdc)(bpe)]⋅DMF (4) (bpdc=4, 4′‐biphenyldicarboxylate; bpy=4, 4′‐bipyridine; 2, 2′dmbpy=2, 2′‐dimethyl‐4, 4′bipyridine; bpe=1, 2‐bis(4‐pyridyl)ethane; DMF=N, N′‐dimethylformamide) to investigate their photoluminescence properties and sensing/detection behavior upon exposure to vapors of various aromatic molecules (analytes) including nitroaromatic explosives. The results show that all four compounds are capable of detecting these molecules in the vapor phase through fluorescence quenching or enhancement. Both electrochemical measurements and theoretical calculations are performed to analyze the analyte–MOF interactions, to explain the difference in signal response by different analytes, and to understand the mechanism of fluorescence quenching or enhancement observed in these systems. Interestingly, compound 3 also shows an emission frequency shift when exposed to benzene (BZ), chlorobenzene (ClBZ), and toluene (TO), which provides an additional variable for the identification of different analytes in the same category.